ANALYSIS OF TEACHER COMPETENCE SOCIAL STUDIES (The Influences of Academic Qualification, Education and Training, and Principal Leadership on Work Motivation and Their Implications on Teacher Competency in State Junior High Schools in Kuningan Regency) - Novi Satria Pradja (Universitas Kuningan, 2018)
Abstract: The subject of social studies is frequently regarded as a difficult one by social studies teachers. The particular problem encountered by the social education at the level of junior high school in Kuningan Regency is the lack of social studies teachers who have the academic background of social studies or social science education. Therefore, based on the survey conducted to junior high schools in Kuningan Regency, many teachers objected to the implementation of Curriculum 2013. This objection reflects the low competency of social studies teachers in the state junior high schools in Kuningan Regency. Based on this background, the problem under research is formulated into the question of how do academic qualification, education and training, principal leadership and work motivation influence competency according to the perceptions of social studies teachers in all state junior high schools in Kuningan Regency. The independent variables in this research are academic qualification (X1), education and training (X2), principal leadership (X3), and work motivation (X4), and the dependent variable is teacher competency (Y). The aim of research to get an idea of the perception of the subject teachers Knowledge of Social Studies (IPS) regarding efforts to improve teacher competence as a professional on the field. The research adopted survey method with data collected from questionnaires distributed to 275 respondents who are social studies teachers from 72 state junior high schools in Kuningan Regency. The findings analyzed with Structural Equation Model (SEM) show that for the first sub-structure, academic qualification, education and training, and principal leadership had positive influences on teachers’ work motivation. The second sub-structure shows that academic qualification, education and training, principal leadership, and work motivation had positive influences on teacher competency. The indirect influences of the variables of academic qualification, education and training, and principal leadership on the variable of work motivation were greater than the direct influences of academic qualification, education and training, and principal leadership on teacher competency.Keywords: Academic qualification, education and training, principal leadership, work motivation, teacher competency.